2017
DOI: 10.37358/rc.17.2.5460
|View full text |Cite
|
Sign up to set email alerts
|

Malondialdehyde and Lipofuscin Biomarkers of Oxidative Stress in Rana temporaria temporaria During Metamorphosis

Abstract: Anuran amphibians metamorphosis represents a model for the study of different processes, including tissue remodeling. One of the body�s systems whose morphological and structural properties are deeply transformed during metamorphosis is the digestive tract. The only structure in the digestive tract which is destroyed and then replaced with a new tissue (histolysis and histogenesis) under the action of oxidative stress and hormones, is the intestinal epithelium. Oxidative stress may be related to the production… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Enterocytes are endowed with an enzymatic charge specific of the larval feedind. They are destroyed and replaced with the juvenile epithelium resulting from the action of the existing cells in the underlying cellular nests [33].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Enterocytes are endowed with an enzymatic charge specific of the larval feedind. They are destroyed and replaced with the juvenile epithelium resulting from the action of the existing cells in the underlying cellular nests [33].…”
Section: Resultsmentioning
confidence: 99%
“…At the level of enterocytes, we observed the changes in the nucleus in relation with the antioxidant enzyme activities. The reactive oxygen species produce oxidative changes in the cell DNA [33]. In the early stages of metamorphosis climax, a condensation of nuclear material is produced and the nuclei appear pyknotics in photon microscopy ( fig.…”
Section: Resultsmentioning
confidence: 99%
“…These vegetative organs contain many active compounds that no longer will be present in the mature plant. In addition, because they contain vitamins, oligoelements and minerals, they are richer in nucleic acids and growth hormones than other vegetal tissues [7][8][9][10][11][12][13][14][15][16][17][18].…”
mentioning
confidence: 99%
“…Recent studies on antioxidants have demonstrated their important role in offset this imbalance [10,11]. Many antioxidant compounds possess antiinflammator y, antiatherosclerotic [12], antiproliferative, antitumor [13], antimutagenic, anticarcinogenic, antibacterial or antiviral activities [13][14][15][16][17][18]. An important group of antioxidants are phenolic compounds [10,12].…”
mentioning
confidence: 99%